Predictors and long-term outcomes of heart block after transcatheter device closure of perimembranous ventricular septal defect - Jiang, Diandong; Zhang, Simiao; Zhang, Yuxin; Lv, Jianli; Yi, Yingchun; Wang, Jing; Wang, Yan; Yang, Xiaofei; Zhang, Jianjun; Han, Bo (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart block is the most common and concerning complication associated with transcatheter device closure of perimembranous ventricular septal defect (pmVSD) and its occurrence remains a great challenge for device closure. Methods: Between June 2002 and June 2020, 1076 pediatric patients with pmVSD, who successfully underwent transcatheter device closure in our center, were enrolled in this cohort study, with a median follow-up of 64 months (range: 1 to 19 years). Results: Of 1076 patients, 234 (21.8%) developed postprocedural heart block, with right bundle branch block being the most common (74.8%), followed by left bundle branch block (16.2%), and atrioventricular block (5.6%). Complete atrioventricular block occurred in 5 cases, including 3 cases with permanent pacemaker implantation, 1 case with recovery to normal sinus rhythm, and 1 case with sudden cardiac death. Most patients (97.9%) developed heart block within one week of procedure. Finally, 138 cases returned to normal cardiac conduction. Multivariate logistic regression revealed that thin-waist occluders (odds ratio [OR]: 1.759; 95% conﬁdence interval [CI]: 1.023 to 3.022; P=0.041), and oversized devices (OR: 1.809; 95% CI: 1.322 to 2.476; P<0.001) were independently associated with occurrence of postprocedural heart block. Moreover, heart block was less likely to occur when the left disc of occluder was placed within the aneurysmal tissue (OR: 0.568; 95% CI: 0.348 to 0.928; P=0.024). Conclusions: The outcome of postprocedural heart block is favorable in most cases. Oversized devices and thin-waist occluders should be avoided. Placement of the left disc of the device should into the aneurysmal tissue is highly recommended.